Cryoballoon Pulmonary Vein Isolation as First-Line Treatment for Typical Atrial Flutter. Issue 5 (17th November 2022) - Gupta, Dhiraj; Ding, Wern Yew; Calvert, Peter; Williams, Emmanuel; Das, Moloy; Tovmassian, Lilith; Tayebjee, Muzahir H; Haywood, Guy; Martin, Claire A; Rajappan, Kim; Bates, Matthew G D; Temple, Ian Peter; et al.
Abstract : Objective: We aimed to compare cryoballoon pulmonary vein isolation (PVI) with standard radiofrequency cavotricuspid isthmus (CTI) ablation as first-line treatment for typical atrial flutter (AFL). Methods: Cryoballoon Pulmonary Vein Isolation as First-Line Treatment for Typical Atrial Flutter was an international, multicentre, open with blinded assessment trial. Patients with CTI-dependent AFL and no documented atrial fibrillation (AF) were randomised to either cryoballoon PVI alone or radiofrequency CTI ablation. Primary efficacy outcome was time to first recurrence of sustained (>30 s) symptomatic atrial arrhythmia (AF/AFL/atrial tachycardia) at 12 months as assessed by continuous monitoring with an implantable loop recorder. Primary safety outcome was a composite of death, stroke, tamponade requiring drainage, atrio-oesophageal fistula, pacemaker implantation, serious vascular complications or persistent phrenic nerve palsy. Results: Trial recruitment was halted at 113 of the target 130 patients because of the SARS-CoV-2 pandemic (PVI, n=59; CTI ablation, n=54). Median age was 66 (IQR 61–71) years, with 98 (86.7%) men. At 12 months, the primary outcome occurred in 11 (18.6%) patients in the PVI group and 9 (16.7%) patients in the CTI group. There was no significant difference in the primary efficacy outcome between the groups (HR 1.11, 95% CI 0.46 to 2.67). AFL recurred in six (10.2%) patients in the PVI arm and one (1.9%) patient in the CTI arm (p=0.116). Time to occurrence of AF of ≥2 min was significantly reduced with cryoballoon PVI (HR 0.46, 95% CI 0.25 to 0.85). The composite safety outcome occurred in four patients in the PVI arm and three patients in the CTI arm (p=1.000). Conclusion: Cryoballoon PVI as first-line treatment for AFL is equally effective compared with standard CTI ablation for preventing recurrence of atrial arrhythmia and better at preventing new-onset AF. Trial registration number: NCT03401099 .